2021
DOI: 10.1186/s12889-021-10327-5
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a secret between us”: a qualitative study on children and care-giver experiences of HIV disclosure in Kinshasa, Democratic Republic of Congo

Abstract: Background It is estimated that 64,000 children under 15 years of age are living with HIV in the Democratic Republic of Congo (DRC). Non-disclosure – in which the child is not informed about their HIV status - is likely to be associated with poor outcomes during adolescence including increased risk of poor adherence and retention, and treatment failure. Disclosing a child’s HIV status to them can be a difficult process for care-givers and children, and in this qualitative study we explored chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…A study in Ghana on children's (6-15 years old) adherence to ART reported that disclosure of HIV status was not only associated with improved adherence but also with psychological well-being [23]. With the disclosure of HIV status, children get cleared with many of their previously unanswered questions concerning the reasons why they were taking medications, engage in peer support groups and ask questions for social support, and improve relationships with caregivers [24,25]. Evidence from a systematic review by Ammon et al also reported that children who received disclosure of their HIV status earlier, before age 12, had good adherence to ART [14].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Ghana on children's (6-15 years old) adherence to ART reported that disclosure of HIV status was not only associated with improved adherence but also with psychological well-being [23]. With the disclosure of HIV status, children get cleared with many of their previously unanswered questions concerning the reasons why they were taking medications, engage in peer support groups and ask questions for social support, and improve relationships with caregivers [24,25]. Evidence from a systematic review by Ammon et al also reported that children who received disclosure of their HIV status earlier, before age 12, had good adherence to ART [14].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn could delay disclosure due to familial stigma and guilt and thereby affect adherence. 28–30…”
Section: Discussionmentioning
confidence: 99%
“…Studies in sub-Saharan Africa (SSA) have shown that the proportion of adolescents to whom HIV disclosure has been done range from as low as 9% (South Africa) to 72% (Ouganda) [ 11 , 12 , 13 ]. This is a result of multiple factors such as parents/caregivers fear of the child disclosing his/her status to others, a lack of knowledge on how the disclosure should be made, considering that the children are young and cannot withstand the psychological impact of diagnosis [ 11 , 14 , 15 ]. It is a real challenge if we want to end the AIDS epidemic by 2030 by achieving 95% diagnosed among all PLHIV, 95% on antiretroviral therapy (ART) among diagnosed, and 95% virally suppressed among treated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%